Entrepreneurial Intentions of Women as Students at Universities in Indonesia: Entrepreneurial Knowledge and Self-Efficacy - Efendi, Riyanto; Tantri, Prisilia Angel (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
Women contribute significantly to a country's economy through entrepreneurship, while women in entrepreneurship are influenced by knowledge and self-efficacy. The purpose of this study was to determine how self-efficacy, through which female students' intentions to pursue entrepreneurship are mediated, interacts with entrepreneurial knowledge. The research method is Explanatory Survey which is analyzed using path analysis techniques. Respondents in this study were female students who had taken entrepreneurship courses totaling 315 female students who were taken using the Proportional Random Sampling method. The results of the study show the important role of entrepreneurial knowledge and self-efficacy in increasing female students' entrepreneurial intentions. First, entrepreneurial knowledge has a positive relationship with female students' entrepreneurial intentions. Second, entrepreneurial knowledge has a positive relationship with female students' self-efficacy. Third, self-efficacy is significantly related to female students' entrepreneurial intentions. Fourth, strong self-efficacy mediates the effect of entrepreneurial knowledge on female students' entrepreneurial intentions.